What Drives Illegal Hunting with Dogs? Traditional Practice in Contemporary South Africa - Chambers, Jaime (Ethnobiology Letters, 2020)
Illegal hunting with dogs in rural South Africa converges around issues of conservation, resource use, and livelihood. Hunting with dogs has a long cultural history, tethered to tradition and subsistence. Today, it is tightly regulated but practiced outside the law. Academic literature and mainstream media alike paint a multidimensional picture of the phenomenon. Some sources portray disenfranchised people practicing a culturally significant livelihood strategy; others emphasize illegal hunting’s destructive nature, severed from traditional context. The drivers of illegal hunting in rural South Africa sit at the nexus of multiple gaps of scholarly insight, linked to a history of widespread stratification of land use, prohibition of traditional hunting, and systematic control of African possession of dogs. There is a need for ethnographic work rooted in environmental history to grapple with the complex connections underlying this issue.